Respuesta :

Answer with explanation:

a)

[tex]x^2+y^2-2x+2y-1=0[/tex]

It could be expressed as:

[tex](x-1)^2-1+(y+1)^2-1-1=0\\\\\\i.e.\\\\\\(x-1)^2+(y+1)^2=3\\\\\\i.e.\\\\\\(x-1)^2+(y+1)^2=(\sqrt{3})^2[/tex]

Hence, the radius of circle is: √3≈1.732 units

b)

[tex]x^2+y^2-4x+4y-10=0[/tex]

It is represented as:

[tex](x-2)^2-4+(y+2)^2-4-10=0\\\\\\i.e.\\\\\\(x-2)^2+(y+2)^2=18\\\\\\(x-2)^2+(y+2)^2=(3\sqrt{2})^2[/tex]

Hence, the radius of circle is: 3√2≈4.242 units

c)

[tex]x^2+y^2-8x-6y-20=0[/tex]

on converting to standard form

[tex](x-4)^2+(y-3)^2=(3\sqrt{5})^2[/tex]

Hence, the radius of circle is: 3√5≈6.708 units

d)

[tex]4x^2+4y^2+16x+24y-40=0[/tex]

on dividing both side by 4 we obtain:

[tex]x^2+y^2+4x+6y-10=0\\\\\\(x+2)^2+(y+3)^2=(\sqrt{23})^2[/tex]

Hence, radius of circle is: √23=4.796 units

e)

[tex]5x^2+5y^2-20x+30y+40=0[/tex]

on dividing both side by 5 we obtain:

[tex]x^2+y^2-4x+6y+8=0[/tex]

[tex](x-2)^2+(y+3)^2=(\sqrt{5})^2[/tex]

Hence, radius of circle is: √5=2.236 units

f)

[tex]2x^2+2y^2-28x-32y-8=0[/tex]

which could also be represented as follows:

[tex]x^2+y^2-14x-16y-4=0\\\\\\(x-7)^2+(y-8)^2=(\sqrt{117})^2[/tex]

Hence, the radius of circle is: [tex]\sqrt{117}[/tex]≈ 10.817 units

g)

[tex]x^2+y^2+12x-2y-9=0[/tex]

It could also be written as:

 [tex](x+6)^2+(y-1)^2=(\sqrt{46})^2[/tex]

Hence, the radius of circle is: [tex]\sqrt{46}[/tex]≈ 6.782 units

            The ascending order is:

        a → e → b → d → c → g → f

Ver imagen Branta
ACCESS MORE